Current Challenges in Pediatric Pulmonary Hypertension - Takatsuki, Shinichi; Ivy, David Dunbar (Seminars in Respiratory and Critical Care Medicine, 2013)
Pulmonary arterial hypertension (PAH) in the pediatric population is associated with a variety of underlying diseases and causes, significantly morbidity and mortality. In the majority of patients, PAH in children is idiopathic or associated with congenital heart disease (CHD), with pulmonary hypertension (PH) associated with connective tissue disease, a rare cause in children. Classification of pediatric PH has generally followed the WHO classification, but recognition of the importance of fetal origins of PH and developmental abnormalities have led to the formation of a new pediatric-specific classification. Incidence data from the Netherlands has revealed an annual incidence and point prevalence of 0.7 and 4.4 for idiopathic PAH and 2.2 and 15.6 for associated pulmonary arterial hypertension-CHD cases per million children. Although the treatment with new selective pulmonary vasodilators offers hemodynamic and functional improvement in pediatric populations, the treatments in children largely depend on results from evidence-based adult studies and experience of clinicians treating children. A recent randomized clinical trial of sildenafil and its long-term extension has led to disparate recommendations in the United States and Europe.
Keywords: pulmonary arterial hypertension; congenital heart disease; children; pediatric pulmonary vascular disease